Metamorphism : material change in architecture - Moravanszky, Akos (Basel : Birkhser, 2018)
'Materiality is a recurring and key issue in architecture. This book explains how materials are'constructed', how they become substances of our culture.'Metamorphism' follows up on the relationship between natural materials and technology, science, and sensuality. Gottfried Semper (1803-1879) made the concept of metabolic processes the key element of his theory. He referred to the fact that architectural forms originally resulting from a method of processing a material are used for other substances. For the first time, the book investigates the subject from a historic point of view whilst reflecting current interdisciplinary findings. Examples from Aalto to Zumthor illustrate the special aspects of erstwhile and contemporary material concepts'--Back cover.
Includes bibliographical references and index.
Keywords: Semper, Gottfried, -- 1803-1879.; Architecture -- Philosophy; Building materials -- History